Strategi Pemasaran Pepaya California di Wairita Farm - Ignatius Moa Toda; Gabriel Otan Apelabi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Strategy is the way in which an institution or organization will achieve its objectives according to the opportunities and threats of the external environment faced and internal capabilities and resources. California variety papaya plant is one type of papaya that began to be much cultivated by farmers. This research aims to find out the marketing strategy of California papaya at Wairita Farm. As for the results of the research obtained that: the strategy that can be applied by farmers managing the California Papaya Farming Business is an Aggressive Strategy formed in quadrant 1. The strategy that wairita farm farmers can implement is growth oriented strategic (supporting aggressive growth policies).